Declarations of Invalidity of a Resolution or Order of a Local Government Body as One of the Measures of Supervision over a Local Authority - Krawczyk, Michał (Management and Administration Journal, 2020)
In this article, basing on normative regulations, judicial decisions of administrative courts and of Constitutional Tribunal and literature of the subject, the analysis of one of the means of supervision over local government was made, which is the Voivode having possibility to state the invalidity of a resolution or order of local government body. Although the legislator equipped the local government with a significant degree of autonomy and independence - legal, judicial, financial, organizational - it did subject the lawfulness of legal acts established by local government bodies to control by government administration bodies and provided for the possibility of declaring them null and void. The article analyses the provisions concerning the circumstances and procedures for the application of such a supervision measure and its implementation as well as the issue of appealing the analysed supervision measure to the administrative court.